2023
DOI: 10.3390/insects14030219
|View full text |Cite
|
Sign up to set email alerts
|

Paving Behavior in Ants and Its Potential Application in Monitoring Two Urban Pest Ants, Solenopsis invicta and Tapinoma melanocephalum

Abstract: Our previous study discovered that two urban pest ants, red imported fire ants, Solenopsis invicta Buren (Formicidae: Myrmicinae), and ghost ants, Tapinoma melanocephalum (Fabricius) (Formicidae: Dolichoderinae), can pave viscose surfaces with particles to facilitate food search and transport. We hypothesize that this paving behavior can be applied to monitor S. invicta and T. melanocephalum. In the present study, 3998 adhesive tapes, each with a food source (sausage), were placed in 20 locations around Guangz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Fire ants usually show many object-use behaviors [30]. For example, our previous studies show that S. invicta usually relocated soil particles to cover the surfaces treated with pesticides, repellents, or sticky materials [18,31,32]. In addition, we observed that S. invicta workers used particles to bury the food under satiation conditions or when the food was treated with repelling chemicals [16].…”
Section: Discussionmentioning
confidence: 91%
“…Fire ants usually show many object-use behaviors [30]. For example, our previous studies show that S. invicta usually relocated soil particles to cover the surfaces treated with pesticides, repellents, or sticky materials [18,31,32]. In addition, we observed that S. invicta workers used particles to bury the food under satiation conditions or when the food was treated with repelling chemicals [16].…”
Section: Discussionmentioning
confidence: 91%
“…Since then, this species has rapidly expanded its range across four continents (North America, Oceania, Africa, and Asia) and numerous islands, owing to its remarkable reproductive capacity and dispersal abilities [ 38 , 39 ]. Currently, S. invicta has become one of the most prevalent ant species in South China [ 40 , 41 , 42 ]. Although RIFA has been acknowledged by certain researchers as a valuable participant in biological pest control across various agricultural domains, such as cotton fields [ 43 , 44 ], sugarcane plantations [ 45 , 46 , 47 ], soybean crops [ 48 ], and greenhouse cultivation [ 49 ], the detrimental consequences it imposes often outweigh its benefits.…”
Section: Introductionmentioning
confidence: 99%